Using network science to evaluate exercise-associated brain changes in older adults - Burdette, Jonathan H.; Laurienti, Paul J.; Espeland, Mark A.; Morgan, Ashley R.; Telesford, Qawi; Vechlekar, Crystal D.; Hayaska, Satoru; Jennings, Janine J.; Katula, Jeff A.; Kraft, Robert A.; Rejeski, Walter J. (Frontiers in Aging Neuroscience, 2010)
Literature has shown that exercise is beneficial for cognitive function in older adults and that aerobic fitness is associated with increased hippocampal tissue and blood volumes. The current study used novel network science methods to shed light on the neurophysiological implications of exercise-induced changes in the hippocampus of older adults. Participants represented a volunteer subgroup of older adults that were part of either the exercise training (ET) or healthy aging educational control (HAC) treatment arms from the Seniors Health and Activity Research Program Pilot (SHARP-P) trial. Following the four-month interventions, MRI measures of resting brain blood flow and connectivity were performed. The ET group’s hippocampal CBF exhibited statistically significant increases compared to the HAC group. Novel whole-brain network connectivity analyses showed greater connectivity in the hippocampi of the ET participants compared to HAC. Furthermore, the hippocampus was consistently shown to be within the same network neighborhood (module) as the anterior cingulate cortex only within the ET group. Thus, within the ET group, the hippocampus and anterior cingulate were highly interconnected and localized to the same network neighborhood. This project shows the power of network science to investigate potential mechanisms for exercise-induced benefits to the brain in older adults. We show a link between neurological network features and cerebral blood flow, and it is possible that this alteration of functional brain networks may lead to the known improvement in cognitive function among older adults following exercise.